ministerial decree 73/2017 amending certain provisions of the ministerial decree 162/2013 - Egypt (2025)
Ministry of Housing, Utilities and Urban Communities Ministerial decree no. 73 of the year 2017 amending certain provisions of the Ministerial Decree No. 162 of the year 2013 approving the rules of recording, Classifying and ranking the members of the Egyptian federation for construction and building contractors وزارة الإسكان والمرافق والمجتمعات العمرانية قرار وزارى رقم 73 لسنة 2017 بتعديل بعض أحكام القرار الوزارى رقم 162 لسنة 2013 باعتماد قيد وتصنيف وترتيب أعضاء الاتحاد المصرى لمقاولى التشييد والبناء